Literacidad y etnografía: La escritura generada en los mercados comerciales - Jiménez Lizama, Pamela Amalia (2015)
This survey describes one of the literacy practices little studied by the sociolinguists, ethnographers and the researchers of the literacies: the writing generated by the merchants in the markets. This way of using the writing is a common literacy practice in many Peruvian commercial markets, not only the buyer elaborates his purchases list, but also the seller usually makes business records and other peculiar annotations, that identify them as social agent, and together with other behavior social patterns and other material conditions that surround them make it a social practice. Therefore, it is important to know the literacy events of buyers and sellers in the markets as a way to know literacy situations beyond school or university; in this way, this paper seeks to explain what and how it is written, and for what purposes it is written. For this, we will be based on the New Literacy Studies (NLS). The survey concludes that writing serves as a cognitive and social tool in a specific social space with specific objectives: to buyers and sellers it allows organizing and memorizing data, and facilitates transactions.